Exploration on the Use of Computerized Accounting Systems by Micro and Small Enterprises (MSEs) in China - Lanlan, Zhang; Ahmi, Aidi (International Journal of Engineering and Technology, 2026)
The main purpose of this study is to investigate the use of Computerized Accounting Systems (CAS) in micro and small enterprises (MSEs) in Xi’an, Shaan Xi of China. The researcher examines the current state of the CAS usage and the software commonly used in China. An online survey has been used to obtain the feedback from 201 respondents. This research finds that 74% of the respondents have used CAS and U8 is the most popular accounting software used by the MSEs in China. While there are a lot of advantages using a survey as data collection tools, there are a few limitations of the method that cannot be avoided. Further research should consider a field study to examine the real issue regarding the CAS implementation in MSEs in China.
Keywords: Computerized Accounting Systems; Micro and Small Enterprises (MSEs); China; Accounting Information Systems